The Use of High Percentages of Fine Ore in a Charcoal Blast-Furnace - Harry R. Hall (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
THE proposition to make pig-iron from magnetic concentrates and cobbed ore with charcoal-fuel weighing from 12 to 20 lb. per bushel is, on the face of it, not inviting; but the successful work that has been done under these adverse conditions warrants a permanent record in our Transactions, especially as it furnishes a comparison with, coke blast-furnace practice under similar conditions. The record of the furnace-practice is briefly summarized as follows:-The charcoal was made of hemlock, pine, spruce, balsam, maple, beech and birch woods. All the concentrates containing from 62 to 65 per cent. of iron would pass in. screen, of which about 34 per cent.. would pass an 80-mesh sieve. The cobbed ore, varying in composition from 32 to 47 per cent. metallic iron and from 23 to 32 per cent. of. silica, would pass through a I-in. ring, of which about 25 per cent. would pass a 1/8 in. screen. The furnace was blown in October 20,1903, with charcoal which was supposed to weigh when dry 18 lb. to the bushel. Some charcoal similar to this was stored in the stock-house for about a year and was then found to weigh 12 lb. per bushel. During the first 10 days of the blast, the furnace produced 362 tons of pig-iron, using 200 bushels of charcoal per ton of iron. From November 1st to 12th, the volume of the blast was increased gradually from 2,808 to 5,460 cu. ft. per minute, with practically no increase of output. The silicon-content of the resultant pig-iron averaged 0.75 per cent., with sulphur about 0.035 per cent. A supply of freshly-burned dry charcoal was then used which increased the silicon-content and lowered